Propuesta de diseño arquitectónico de un equipamiento cultural ubicado en el vacío urbano C8 en el centro histórico de Riobamba - Suárez López, Catherine Roxanna (2022)
Riobamba was the first-ever planned city in the country, which resulted in the design of a Historical Center with a remarkable cultural value, where plenty of historical architectonic pieces can be found. These pieces' beauty and cultural heritage, primarily Republican designs, allowed Riobamba to be declared a National Cultural Heritage. Which has architectural samples mostly republican, for its beauty and relevance made the city be declared as Cultural Patrimony of the nation. The lack of cultural activities in the city affected one of the emblematic buildings of the historical center, Teatro León, to suffer years of abandonment and destruction, and the presence of an urban void next to the building degraded the urban image and culture of the city for a long time. The city lacks facilities that encourage art education and culture, The lack of this type of space has meant that cultural facilities, such as Teatro León, do not function properly, preventing the city from having a dynamic cultural agenda. In order to complement these buildings and given this problem, it seeks to recover a space considered an urban and social void, proposing a cultural facility for artistic education that generates cultural activity, which is directly related to its immediate surroundings and is correctly inserted in the heritage context. The proposal comprises three levels; on the first floor, there are public and permeable spaces that establish visual and pedestrian connections with the surroundings; the second floor is dedicated to art education; and on the third floor, a cafeteria that connects directly with Teatro León. A network of public spaces is created in the city, in which this facility becomes an essential element since it provides connection and dynamism in the sector and promotes a culture in the city